# math/algebra

posted by Diana

solve each of the following systems by substitution.
16) 5x -2y = -5
y - 5x = 3
20) 8x -4y = 16
y = 2x - 4
28) 4x -12y = 5
-x + 3y = -1

Step one: Solve on of the equations for one of the variables.
y=2x-4
Step two:Substitute the expression for the variable found in step one into the other equation.
8x-4(2x-4)=16
Step three:Solve the equation from step two to find the value of one variable.
Use the distributive property
8x-4(2x-4)=16
8x-8x+16=16
x+16=16
-16 -16
x=0
Step four:Substitute the value found in step three in any equation containing both variables to find the value of the other variable.
y=2x-4
y=2(0)-4
y=0-4
y=-4
step five: check the proposed solution in the orginal system.
8(0)-4(-4)=16
0+16=16
16=16
The equation is equal, so it is correct.
#28
4x-12y=5 -x+3y=-1
+x +x
3y=-x or -3y=x

4(-3y)-12y=5 4x-12(5)=5
-12y-12y=5 4x-60=5
y=5 +60 +60
4x=65
x=65/4

4(65/4)-12(5)=5
260/4 - 60=5
65 - 60 = 5
5 = 5
it's correct

I hope I helped

## Similar Questions

1. ### Algebra

Can someone show me step by step how to do this problem to have an example to go by so I will be able to do my other problems. Thanks Solve by substitution 4x-12y=5 -x+3y=-1 I know that you have solve one of the equations. I have picked …
2. ### Algebra 1

solve each following system by substitution 4x-12y=5 -x+3y=-1
3. ### Algebra 1

solve each following system by substitution. 4x-12y=5 -x+3y=-1
4. ### algebra

Solve the following systems by substitution. 4x-12y=5 -x+3y=-1
5. ### math

Solve this system 4x-12y=5 ,-x+3y=-1 by substitution
6. ### Algebra

How do I solve the following by substitution: 5x -2y =-5 y - 5x = 3 8x - 4y = 16 y = 2x - 4 4x -12y =5 -x + 3y = -1
7. ### Algebra

How to solve by substitution: 4x - 12y=5 -x + 3y = -1
8. ### algebra

Solve by substitution; 4x-12y=5 -x+3y
9. ### Algebra

Solve by substitution: 4x-12y =5 -x + 3y = -1